IgG-based B7-H3xCD3 bispecific antibody for treatment of pancreatic, hepatic and gastric cancer - Lutz, Martina S.; Zekri, Latifa; Weßling, Laura; Berchtold, Susanne; Heitmann, Jonas S.; Lauer, Ulrich M.; Jung, Gundram; Salih, Helmut R. (Frontiers in Immunology, 2023)
T cell-based immunotherapy has significantly improved treatment options for many malignancies. However, despite these and other therapeutic improvements over the last decades, gastrointestinal cancers, in particular pancreatic, hepatic and gastric cancer, are still characterized by high relapse rates and dismal prognosis, with an accordingly high unmet medical need for novel treatment strategies. We here report on the preclinical characterization of a novel bispecific antibody in an IgG-based format termed CC-3 with B7-H3xCD3 specificity. In many cancer entities including pancreatic, hepatic and gastric cancers, B7-H3 (CD276) is overexpressed on tumor cells and also on the tumor vasculature, the latter allowing for improved access of immune effector cells into the tumor site upon therapeutic targeting. We demonstrate that CC-3 induces profound T cell reactivity against various pancreatic, hepatic and gastric cancer cell lines as revealed by analysis of activation, degranulation and secretion of IL2, IFNγ as well as perforin, resulting in potent target cell lysis. Moreover, CC-3 induced efficient T cell proliferation and formation of T cell memory subsets. Together, our results emphasize the potential of CC-3, which is presently being GMP-produced to enable clinical evaluation for treatment of pancreatic, hepatic and gastric cancer.